INVESTIGATING THE IMPACT OF FRIENDS, CELEBRITIES, OPINION LEADERS, SOCIAL VALUE AND PERSONAL VALUE ON PURCHASE INTENTION OF LUXURY FASHION CONSUMERS IN JAKARTA - Valeta, Nesya Verdelia; Ruslim, Tommy Setiawan (International Journal of Application on Economics and Business, 2023)
The Covid-19 outbreak caused an uproar throughout the world, including Indonesia, March 2, 2020 was a silent witness where it was first reported that the Covid-19 virus had entered Indonesia. The Covid-19 phenomenon has finally changed the way people live, from which initially they could meet face-to-face, but now meetings can only be done online. Of course, all industries are starting to adapt to the COVID-19 conditions, including the luxury fashion industry, which has experienced a decline in sales during the COVID-19 pandemic and has increased again through adaptation through social media. This is related to the purchase intention of luxury fashion consumers. The purpose of this study was to determine empirically the effect friends, celebrities, opinion leaders, social value, and personal value on purchase intention of luxury fashion consumers in Jakarta. This study uses data obtained from 215 respondents who are over 18 years old and are luxury fashion consumers who live in Jakarta. The data was obtained by distributing an online questionnaire in the form of a google form through social media. The data is then processed using SmartPLS 3.2.9 software. The results of this study are friends, celebrities, opinion leaders, social value and personal value have a positive and significant influence on the purchase intention of luxury fashion consumers in Jakarta.